Absolute Paleolatitude of Northern Zealandia From the Middle Eocene to the Early Miocene. Issue 9 (16th September 2022) - Dallanave, Edoardo; Sutherland, Rupert; Dickens, Gerald R.; Chang, Liao; Tema, Evdokia; Alegret, Laia; Agnini, Claudia; Westerhold, Thomas; Newsam, Cherry; Lam, Adriane R.; Stratford, Wanda; Collot, Julien; et al.
Abstract: The absolute position during the Cenozoic of northern Zealandia, a continent that lies more than 90% submerged in the southwest Pacific Ocean, is inferred from global plate motion models, because local paleomagnetic constraints are virtually absent. We present new paleolatitude constraints using paleomagnetic data from International Ocean Discovery Program Site U1507 on northern Zealandia and Site U1511 drilled in the adjacent Tasman Sea Basin. After correcting for inclination shallowing, five paleolatitude estimates provide a trajectory of northern Zealandia past position from the middle Eocene to the early Miocene, spanning geomagnetic polarity chrons C21n to C5Er (∼48–18 Ma). The paleolatitude estimates support previous works on global absolute plate motion where northern Zealandia migrated 6° northward between the early Oligocene and early Miocene, but with lower absolute paleolatitudes, particularly in the Bartonian and Priabonian (C18n–C13r). True polar wander (solid Earth rotation with respect to the spin axis), which only can be resolved using paleomagnetic data, may explain the discrepancy. This new paleomagnetic information anchors past latitudes of Zealandia to Earth's spin axis, with implications not only for global geodynamics, but also for addressing paleoceanographic and paleoclimate problems, which generally require precise paleolatitude placement of proxy data. Plain Language Summary: The ancient latitude (paleolatitude) of a tectonic plate can be determined from magnetism recorded in rocks (paleomagnetism). Earth's geomagnetic field, averaged over geological time, is symmetrical around Earth's spin axis. Hence, the direction of the remanent magnetization in rocks can provide the paleolatitude and orientation of a tectonic plate with respect to the geographic poles. Using marine sediments recovered during International Ocean Discovery Program Expedition 371, we present five paleolatitude estimates for northern Zealandia, a mostly submerged continent in the southwest Pacific encompassing New Zealand and New Caledonia. The reconstructed paleolatitudes span the time interval from 48 to 18 million years ago (middle Eocene to middle Miocene), and represent the first such estimates from northern Zealandia. Geodynamic models for Earth surface motion relative to the spin axis require several assumptions and do not accurately predict our results. Combined with data from other continents, a more precise reconstruction for Zealandia's past geography has implications for understanding various fossil records in this extensive region, including those important for past ocean circulation and climate models, and for the evolution of plants and animals. Key Points: We present five paleomagnetic‐based absolute paleolatitudes for northern Zealandia during the middle Eocene–early Miocene Paleolatitude estimates are based on paleomagnetic directions from two deep‐sea cores drilled in the Tasman Sea Precise absolute paleolatitudes underpin accurate paleogeography, with implications for paleoclimate modeling